PTU-179 The clinical significance of sensory abnormalities in irritable bowel syndrome. (22nd June 2015) - Eugenicos, MP; Syme, PD; Moore, D
Abstract : Introduction: Altered pain appreciation and autonomic function are features of Irritable Bowel Syndrome (IBS); these are controlled by the lateral medulla (LM). Abnormal vasomotor control, sweating, cardiac rhythm, blood pressure and gut motility have all been reported in the LM Syndrome. Our aim was to study LM features and characterise these in IBS patients and healthy controls. Method: Patients attending a specialist Motility clinic were asked to complete the Rome III and the Hospital anxiety/depression (HAD) questionnaires. Sensory abnormalities were assessed with a temperature appreciation (TA) test; reporting on cold sensation by holding a glass of ice-cold water in each hand consecutively for 5 s. The age, sex, blood pressure, heart rate, Rome III and HAD questionnaires were recorded along with TA. Medical students served as healthy controls. Data was analysed and compared between the patients and students. The chi-square and Mann-Whitney tests were used to assess the association between IBS and sensory abnormalities and IBS and HAD scores respectively. Results: 133 patients (116 females: 17 males; mean age 51 years: range 19–89) and 35 students (23 females:12 males; mean age 23 years: range 19–27) completed the ROME III questionnaires. IBS-M (mixed type) was the most common with 43 patients (32%), followed by 39 patients (29%) with IBS-C (constipation), 29 patients (21%) with IBS-D (diarrhoea) and 22 patients had other functional disorder (18%). 28 (80%) students had no IBS symptoms, but 3 had IBS-M (8.5%), 3 had IBS-C (8.5%) and 1 had IBS-D (3%). IBS patients had higher anxiety (8 vs 4; p < 0.005) and depression (6 vs 1; p < 0.005) scores as compared to the non-IBS students. 94 IBS patients undertook the TA test: 41 experienced equal (44%) and 53 reported unequal (56%) sensation in their hands, whereas 27 students reported equal (96%) and only 1 unequal (4%) sensation. The null hypothesis that there is no association between IBS and sensory abnormalities was rejected (P < 0.005). Conclusion: The ROME III Criteria is useful for identifying IBS subtypes. We found a significantly higher degree of both anxiety and depression and altered temperature appreciation in this group of IBS patients. The clinical significance of the latter is unclear. Further studies are warranted to determine whether the findings are organic or functional. Disclosure of interest: None Declared.